Tatalaksana Perawatan Intensif Pasien PPOK Eksaserbasi Akut dengan Gagal Napas Tipe II - Widodo, Untung; Adiyanto, Bowo; Aprianti, Tutut (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2019)
A fifty-two years old male was diagnosed COPD with acute exacerbation had care in intensive care unit for 7 days. Patient hospitalized for dyspneu, decreased consciousness and was diagnosed with acute exacerbation of obstructive pulmonary disease with mix type of respiratory failure. Patient was intubated, mechanically ventilated, and given COPD medical therapy during ICU treatment. Routine blood gas analysis and chest X-rays evaluation has been done to determine the improvement of ventilation. Ventilator weaning was performed so that the patient can breathe adequately and blood gas analysis showed improve.